Manajemen Asuhan Kebidanan Keluarga Berencana pada Ny “J” Akseptor KB Suntik 3 Bulan dengan Kenaikan Berat Badan di PMB Hj. Nurhaedah Kab. Bone: Management of Family Planning Midwifery Care for Ny “J” 3 Months Injectable KB Acceptor with Weight Gain at PMB Hj. Nurhaedah, Bone Regency - Ita Novianti; Kiki Reski Rahmadani Bakri; Suci Rahayu (Jurnal Midwifery, 2023)
Introduction Hormonal contraception 3 month injection in Depo-Medroxy Progesterone Acetate (DMPA) is one method of contraception that is in great demand. Have good effectiveness, but it also has side effects such as menstrual disorders, spotting bleeding and bleeding in the menstrual cycle. In addition, there is also an increase in body weight gain is caused by the hormone progesterone, which makes it easier to change carbohydrates and sugar turns into fat, previous studies showed that the percentage of weight gain due to the use of DMPA was 69%. The importance of proper care and high weight gain due to DMPA, so that the purpose of this research was to provide midwifery care family planning acceptors of 3-month injecting family planning with weight gain in PMB Hj. Nurhaedah according to the needs and authority of midwives. Method This research used the 7-step midwifery care management method Varney and SOAP. Result Base on the case studies that have been conducted, it shows that the mother remains a acceptor of 3-month injections and accepts the side effects she experiences, namely weight gain. Conclusion This case study of 3-month injection family planning acceptors with weight gain at PMB Hj. Nurhaedah an analysis and documentation study was carried out regarding all the actions that had been carried out with results no discrepancy was found between the theory and the cases obtained